Electrothermal effect on the immunoassay in a microchannel of a biosensor with asymmetrical interdigitated electrodes. (25th July 2016) - Selmi, M.; Khemiri, R.; Echouchene, F.; Belmabrouk, H.
Graphical abstract: Highlights: AC electro-thermal flow and heat generation have been studied. The temperature boundary condition influences significantly the binding rate. Highest electrical conductivity causes the stronger electrothermal flow. Lower substrate thermal conductivity raises the binding rate. Abstract: In this paper, we study the AC electrothermal (ACET) effect on the binding reaction of immunoassays which a ligand (anti-C-reactive protein) immobilized on a microchannel wall specifically binds analyte (C-reactive protein (CRP)) flowing through a configuration of a microchannel with asymmetrical planar electrode pairs. The Navier–Stokes equations coupled with the Laplace and energy equations, the Fick's second law in convection–diffusion coupled with the first order Langmuir adsorption model are used. The set of equations is solved in a two-dimensional configuration using the finite element method. Three cases of the thermal boundary conditions are investigated to study the effect of the temperature field on the binding reaction efficiency. The electrical conductivity of the buffer solution, the thermal conductivity of the base material and the surface reaction length are also discussed in this work. The simulation results show that the heterogeneous immunoassay is improved when the external surfaces of the cover and the substrate are kept at a constant temperature. For the best case studied in this work, the enhancement factors of the binding curve can be raised up to 3.46 and 2.84 for the association and dissociation phases, respectively, with 4 Vrms applied voltage and operating frequency of 100 kHz and electrical conductivity of 0.01 S/m.